2005
DOI: 10.1002/masy.200551412
|View full text |Cite
|
Sign up to set email alerts
|

Role of Hemicelluloses in the Formation of Chromophores During Heat Treatment of Bleached Chemical Pulps

Abstract: The heat-induced colour formation of TCF-and ECF-bleached chemical pulps has been investigated. Partial hydrolysis of the pulps and analysis of the carboxyl content of the pulps and hydrolysed matter were carried out. It was found that the yellowing tendency of the pulps corresponds to the content of hydrolysable substances. The hydrolysis leads to a considerable removal of the carboxyl groups in the case of hardwood pulps. Differences between softwood and hardwood pulps are discussed in terms of their hemicel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 18 publications
1
15
0
1
Order By: Relevance
“…A lower hemicellulose content may, however, lead to a less extensive oxidation of the pulp (Figure 2c) and this fact can indirectly affect the brightness stability. This result correlates quite well with that obtained in previous studies investigating the role of hemicelluloses on pulp yellowing (Vuorinen et al 1999;Beyer et al 2006).…”
Section: Brightness Stabilitysupporting
confidence: 92%
See 1 more Smart Citation
“…A lower hemicellulose content may, however, lead to a less extensive oxidation of the pulp (Figure 2c) and this fact can indirectly affect the brightness stability. This result correlates quite well with that obtained in previous studies investigating the role of hemicelluloses on pulp yellowing (Vuorinen et al 1999;Beyer et al 2006).…”
Section: Brightness Stabilitysupporting
confidence: 92%
“…Other factors, which are often considered to have a less pronounced effect on pulp brightness reversion, include metal ions, pH, etc. (Gullichsen and Söderhjelm 1984;Chirat and Chapelle 1999;Grandström et al 2001;Beyer et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…A likely cause of the phenomenon is attributed to more hemicellulose and HexA contents in wheat straw CP and more lignin in poplar CTMP. Hemicellulose polysaccharides, because of their relatively low degree of polymerization, were easily hydrolyzed to low-molecular carbohydrate compounds, which subsequently underwent dehydration and condensation reactions to form chromogenic substances2728; HexA is also easily degraded during heat- and light-induced yellowing to generate colored compounds27. Increased xylanase dosages led to enhanced hemicellulose removal, for example, hemicellulose content of wheat straw CP is 13.6% and 12.8% when xylanase dosages are 20 and 80 U/g, respectively, thus decreases pulp PCN.…”
Section: Resultsmentioning
confidence: 99%
“…Beyer et al (2006) found heat induces thermal processes which usually lead to non-beneficial effects such as yellowing, discoloration, or unpleasant odor. In earlier studies discoloration of birch had been investigated using colorimetric methods, with results indicating a notable color change occurring during kiln drying, of which temperature appeared to be the most important parameter (Kreber and Haslett, 1997;Luostarinen and Verkasalo, 2000;Kreber et al, 2001;Luostarinen and Luostarinen, 2001;Mononen et al, 2002;Sundqvist, 2002;Mononen et al, 2004).…”
Section: Causes Of Wood Discoloration 41 Heatmentioning
confidence: 99%